Performance Of Internal Combustion Engine Using Fuel From Biomass - Yap, Chui Sheng (Universiti Sains Malaysia, 2005)
The use of biomass for energy generating is getting increasing attention because of the energy reserves such as gas and oil is decreasing. At present, biomass gasification is taken as a popular technical route to produce fuel gas for application in engine. The use of producer gas as an alternative to diesel in engines has advantage from both economic and environmental perspective. The sources of biomass are easy to found and the biomass energy reduce the level of disposal and pollution in this world. Today, with this renewable energy technologies petroleum or diesel consumption can be reduced and substituted partly by alternative fuels in engine. The objective of this project is to assembly the experimental rig of a diesel engine using producer gas from gasification system and also to present some experimental result. The 20 kWth downdraft gasifier was used to produce gas with off-cut furniture wood with moisture content 6.2% used as biomass material. Cussons Single Cylinder Engine Test Bed which consists of Yanmar L60AE-DTM single cylinder diesel engine and dynamometer has also been used in this experiment. The combustion characteristic and performance characteristic for diesel engine and mixture of diesel and producer gas were compared. The result indicated that dual fuel engine has similar combustion characteristic to diesel engine. The performance of dual fuel engine is lower compared to diesel engine. The usage of producer gas in diesel engine can reduce the consumption of diesel fuel for combustion process which is about 170%. In addition, studies using blend of diesel and waste cooking oil are presented for comparison.